Amyotrophic lateral sclerosis : exercise and disease progression - M.A.Braga, Anna Caroline (2018)
Amyotrophic Lateral Sclerosis (ALS) belongs to a group of neurological disorders known as motor neuron diseases, which are caused by gradual degeneration and consequent death of motor neurons. In general, the disease begins in one of two fundamental ways: with involvement of the muscles of the bulbar region; or with loss of muscle strength of the upper or lower limbs - spinal form. Although other rare forms of manifestation are also cited in the literature, such as: respiratory (when respiratory muscles are initially affected); axial (initially affecting the cervical and paraspinal muscles) and the diffuse form (generalized onset of the disease). These forms of presentation determine the initial symptoms. Patients may initially develop muscle weakness in the limbs resulting in various clinical conditions with paresis, speech problems with dysarthria, dysphagia, and respiratory symptoms with dyspnea, and evolve to complete loss of body movements control. The degree of functional disability and dependence resulting from ALS lead the patient to gradually needing a caregiver for all their activities of daily life. The mean survival for ALS is around 3 - 5 years from first symptoms, and the fatal event usually occurs due to respiratory failure or infection. Although there is no effective treatment to halt disease progression, the clinical management has evolved positively in last years. The technological advance of medical interventions has contributed to a longer survival and higher quality of life. The monitoring of non-invasive ventilation has been very helpful for the clinical follow up and to decrease the anxiety experienced by caregivers. Unfortunately, the aerobic exercise is not a usual therapeutic option for ALS patients in the clinical management yet. Physical exercise has been suggested to promote growth factor delivery in experimental animal models of ALS. However, the aerobic exercise is understudied in ALS patients due the suspicious that the exercise could be harmful for this population. Meeting the recommendations from the last Cochrane review about Therapeutic exercise in ALS, we have analyzed the impact of aerobic exercise in the ALS progression. This thesis has 2 main contributions: 1 - To study the efficacy of moderated and accurate defined exercise program on the evolution and survival of ALS, and, 2 - to assess the feasibility to performing exercise monitored remotely from home in ALS patients. In addition, this thesis includes results from additional contributions, which are related to relevant issues always present during disease progression such as management of the respiratory failure (sub-chapters 5.2 and 5.3), the support for ALS caregivers (Chapter 6), and the potential impact of clinical management on disease progression in an environment with lack of resources (Chapter 7). In the sub-chapter 5.2 we present a work which describe the lack of consensus for the ideal timing to start NIV and about the use of alternative respiratory support. We address the impact of NIV and tracheostomy on family and / or informal caregivers, especially how it can affect quality of life. The importance of assessing the emotional, physical, social and psychological capacity of the caregiver is reinforced in order to cope with the increasing care needs of these patients. The sub-chapter 5.3 presents results on the importance of a careful management in the use and configuration of Non-Invasive Ventilation (NIV) parameters, in particular the role of ventilation and adherence adjustments in functional decline and survival of ventilated patients. A wide range of data recorded from the software used in ventilators, nocturnal pulse oximetry measurements and respiratory function tests were analyzed. Our results suggest that the variables that affect the respiratory comfort of the patient are relevant for adherence to NIV and positively affect survival in ALS. The Chapter 6 presents results of a feasibility study about a training program for caregivers. The uncertain progression of the disease and long-term care, as well as the insufficient number of skilled health professionals, determine that the admission of these patients to hospitals or to continuing care units is a complex option. Initiatives that allow better management of the disease at home can be an alternative solution. The functional disability of patients can promote significant financial constraints, and exposes their families to high levels of stress, which can compromise the provision of adequate health care, leading to the hospitalization of these patients. In this project, we identified an excellent level of participation as well as a good result in the evaluation of learning (above 70%). The main limiting factor for participation in the training program was the absence of a secondary caregiver. The Chapter 7 describes results from2 studies conducted with ALS patients in the African continent, which present data on disease progression in an environment with limited resources for clinical management. The Chapter 8 present a general discussion and conclusion of all works included in this Thesis. All the papers presented in this thesis aim to contribute to a broader view of the clinical management of ALS, where the role of exercise associated with more careful respiratory support, and the presence of a well-informed and trained caregiver, can together be an important contribution for the survival and quality of life of the patient with ALS. We hope our work presented in this thesis may contribute to a wider understanding on the clinical management of ALS. In particular demonstrating that controlled exercise associated with careful respiratory support, and the presence of a well-informed and trained caregiver, may be an added value in the survival and quality of life for ALS patient.